Redox Balance in Male Infertility: Excellence through Moderation—“Μέτρον ἄριστον” - Evangelos N. Symeonidis; Evangelini Evgeni; Vasileios Palapelas; Dimitra Koumasi; Nikolaos Pyrgidis; Ioannis Sokolakis; Georgios Hatzichristodoulou; Chara Tsiampali; Ioannis Mykoniatis; Athanasios Zachariou; Nikolaos Sofikitis; Ares Kaltsas; et al. (Antioxidants, 2021)
Male infertility, a relatively common and multifactorial medical condition, affects approximately 15% of couples globally. Based on WHO estimates, a staggering 190 million people struggle with this health condition, and male factor is the sole or contributing factor in roughly 20–50% of these cases. Nowadays, urologists are confronted with a wide spectrum of conditions ranging from the typical infertile male to more complex cases of either unexplained or idiopathic male infertility, requiring a specific patient-tailored diagnostic approach and management. Strikingly enough, no identifiable cause in routine workup can be found in 30% to 50% of infertile males. The medical term male oxidative stress infertility (MOSI) was recently coined to describe infertile men with abnormal sperm parameters and oxidative stress (OS), including those previously classified as having idiopathic infertility. OS is a critical component of male infertility, entailing an imbalance between reactive oxygen species (ROS) and antioxidants. ROS abundance has been implicated in sperm abnormalities, while the exact impact on fertilization and pregnancy has long been a subject of considerable debate. In an attempt to counteract the deleterious effects of OS, urologists resorted to antioxidant supplementation. Mounting evidence indicates that indiscriminate consumption of antioxidants has led in some cases to sperm cell damage through a reductive-stress-induced state. The “antioxidant paradox”, one of the biggest andrological challenges, remains a lurking danger that needs to be carefully avoided and thoroughly investigated. For that reason, oxidation-reduction potential (ORP) emerged as a viable ancillary tool to basic semen analysis, measuring the overall balance between oxidants and antioxidants (reductants). A novel biomarker, the Male infertility Oxidative System (MiOXSYS®), is a paradigm shift towards that goal, offering a quantification of OS via a quick, reliable, and reproducible measurement of the ORP. Moderation or “Μέτρον” according to the ancient Greeks is the key to successfully safeguarding redox balance, with MiOXSYS® earnestly claiming its position as a guarantor of homeostasis in the intracellular redox milieu. In the present paper, we aim to offer a narrative summary of evidence relevant to redox regulation in male reproduction, analyze the impact of OS and reductive stress on sperm function, and shed light on the “antioxidant paradox” phenomenon. Finally, we examine the most up-to-date scientific literature regarding ORP and its measurement by the recently developed MiOXSYS® assay.